Implementing Law Enforcement to Corporate Social Responsibility (CSR) Violations by Companies - Agustin, Nely; Sulaksono, Agam; Romadhon, Ahmad Heru (Journal of Progressive Law and Legal Studies, 2025)
All parties, both government and non-governmental, such as company multinational and non-governmental organizations, must work together to realize this global agenda, reach SDGs goals and targets, and implement sustainable development. The company focuses on sustainable development issues Because of Regulation Presidential Decree No. 59 of 2017 concerning the Implementation Achievement of Sustainable Development Goals. Following Constitution Number 40 of 2007 concerning Limited Liability Companies, liability answer social (CSR) is an obligation company to society. In this matter, the government is expected to keep driving the business world to implement CSR correctly, appropriately, and appropriately with purpose. Using data collection analysis and qualitative research, this paper aims to explain how the company implements CSR and how CSR violations cause punishment to the company. This research shows that the company must not quite adequately answer social (CSR) questions in the right way to the needs of society. In implementing activity responsibility, the company will get a consequence law in the form of sanctions if every regulation implementation of TJSL is violated. The provision of sanctions is under legislation that has been determined so that the company can comply with obligations that should be done to improve the public's welfare.